Proses Penciptaan Manusia Dan Implikasinya Pada Pembelajaran Pendidikan Agama Islam Di Prodi Kedokteran UNKHAIR: Satu Telaah Tafsir Maudhui Dan Ilmu Pengetahuan Sains - Alhaddad, Bujuna A.; Haddade, Hasyim; Damis, Rahmi (STIT Muhammadiyah Paciran Lamongan, 2022)
The last holy book that was revealed by Allah to our last Apostle, namely the Prophet Muhammad, namely the Qur'an as a guide and way of life for mankind. It is used as a norm and value in addition to the sunnah, in introducing itself the Qur'an as a hudal Alnas is a guide for mankind. Humans in the Qur'an as monodual, two-dimensional humans consisting of physical and spiritual elements are seen as the main, perfect noble creatures among all of God's creations. This study aims to examine the verses of the Qur'an related to scientific knowledge about the process of human creation. In this study the author uses a qualitative method with the type of literature research with a maudhui interpretation approach and a medical science approach. The results and discussion found that after Prophet Adam, the process of human creation through several stages of creation and among them are nutfa, alaqah, mudgah, bone and muscle making, then perfected by blowing the spirit so that the best form is created, which is called human. The stages of human creation are gametogonesis, the process of ovulation to implantation, then the bilaminar gendisc, the embryonic period to the stage of childbirth.